An evaluation of flexible fibreoptic sigmoidoscopy. Issue 6306 (12th December 1981) - Vellacott, K D; Hardcastle, J D
Abstract : Results of 350 flexible fibreoptic sigmoidoscopy examinations showed a diagnostic yield of 30% compared with 6.5% by rigid sigmoidoscopy of the same patients. The mean time for the examinations was eight minutes, a distance of over 50 cm being visualised in 65% of the patients. Preparation of the bowel with a single phosphate enema was adequate in 95% of the patients. As an outpatient investigation for clinicians fibreoptic sigmoidoscopy is a safe, quick, and useful addition to rigid sigmoidoscopy and should result in a decrease in the number of barium enema examinations required.